Critical nitrogen dilution curve and nitrogen nutrition index for jute mallow (Corchorus olitorius L.) In southern Benin - Huat, J.; Touré, A.; Tanaka, A.; Amadji, G. (Cambridge University Press, 2018)
Indigenous crops, such as jute mallow (Corchorus olitorius L.) have high potential for improving nutrient efficiency and income source diversification of farmers in sub-Saharan Africa. A better understanding of plant responses to nitrogen (N) is essential in shedding light on the trend towards increasing fertilizer applications for commercially grown jute mallow. The aim of this study was to determine the critical N dilution curve in order to assess the N nutrition index (NNI) in jute mallow in southern Benin. Above-ground dry matter (DM) and N concentration were determined weekly during the 2010 and 2011 growing seasons and six N treatments of 0, 30, 60, 120, 180 or 240 kg N ha−1 were tested under irrigated conditions. A critical N curve (Nc = 3.35 W−0.18), where W is the DM in Mg per ha, was plotted based on the N concentration in the whole plant. The critical N concentration (Nc) represents the minimal N concentration required to achieve maximum growth. According to significant differences in DM at each sampling date, data points were divided into two groups representing either N deficient or N excess conditions. All data points in the N deficient group were under the critical N curve and most data points in the N excess group were on or above the critical N curve, therefore confirming the validity of the critical N curve determined in southern Benin. The NNI calculated as the ratio between the measured N concentration and predicted Nc, ranged from 0.55 to 1.30. The equation for the critical N curve and NNI determined in this study for jute mallow could potentially be used as a parameter for N application under non-deficient water conditions in southern Benin.